Stochastic source seeking with forward and angular velocity regulation. (September 2017) - Lin, Jinbiao; Song, Shiji; You, Keyou; Krstic, Miroslav
Abstract: This paper studies a stochastic extremum seeking method to steer a nonholonomic vehicle to the unknown source of a spatial field in a plane. The key challenge lies in the lack of vehicle's position information and the distribution of the scalar field. Different from the existing stochastic strategy that keeps the forward velocity constant and controls only the angular velocity, we design a stochastic extremum seeking controller to regulate both forward and angular velocities simultaneously in this work. Thus, the vehicle decelerates near the source and stays within a small area as if it comes to a full stop, which solves the overshoot problem in the constant forward velocity case. We use the stochastic averaging theory to prove the local exponential convergence, both almost surely and in probability, to a small neighborhood near the source for elliptical level sets. Finally, simulations are included to illustrate the theoretical results.